2020
DOI: 10.1097/ncq.0000000000000463
|View full text |Cite
|
Sign up to set email alerts
|

Staff Working Life and Older Persons' Satisfaction With Care

Abstract: Background: The importance of staff working life for staff well-being has been demonstrated in several studies; less research has focused on staff working life and older persons' satisfaction with care. Purpose: The study aim was to study relationships between 1) staff assessments of their structural conditions/empowerment in elderly care, psychological empowerment, and job satisfaction and (2) older persons' satisfaction with care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Furthermore, that empowering workplaces retain nurses and prevent burnout (Meng et al, 2015). Additionally, positive relationships were found between staffs' access to structural empowerment and patient satisfaction (Engström et al, 2021), staff‐rated quality of care (Engström et al, 2011), professional nursing practice behaviours (Manojlovich, 2010) and evidence‐based practice (Engström et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, that empowering workplaces retain nurses and prevent burnout (Meng et al, 2015). Additionally, positive relationships were found between staffs' access to structural empowerment and patient satisfaction (Engström et al, 2021), staff‐rated quality of care (Engström et al, 2011), professional nursing practice behaviours (Manojlovich, 2010) and evidence‐based practice (Engström et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…First‐line managers (FLMs) play a central role in providing access to these structures. Studies have shown links between the nursing staff's perceived access to empowering structures in the workplace and positive outcomes for both staff (Cicolini et al, 2014; Engström et al, 2011) and patients (Engström et al, 2021). FLMs should provide their staff access to empowering structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maria et al . demonstrated that the job satisfaction of care providers has a significant impact on older person's satisfaction with care 26 . Our study findings can be utilised for better healthcare planning in Japan and other super‐ageing countries.…”
Section: Discussionmentioning
confidence: 64%
“…Maria et al demonstrated that the job satisfaction of care providers has a significant impact on older person's satisfaction with care. 26 Our study findings can be utilised for better healthcare planning in Japan and other superageing countries. However, we have not explored the barriers and challenges in a geriatric career, which demands the scope for future research.…”
Section: Discussionmentioning
confidence: 75%